Determination of In-vitro Biochemical Activities of Reflevone, A New Natural Organic Compound. Issue 6 (2nd November 2017) - Oladimeji, Abdulkabir Oladele; Oladosu, Ibrahim Adebayo; Khan, Ajmal
Abstract: A number of studies have shown that flavonoids possess numerous pharmacological properties such as antioxidant and anticancer effects. The study sought to determine the immunomodulatory, urease inhibitory, free radicals scavenging and cytotoxic activities of reflevone, a new flavonoid recently isolated from roots of Dioclea reflexa (Hook. F.). Reflevone, showed a very strong immunosuppressant effect on phytohaemagglutinin (PHA) stimulated T-cell (IC50 : 6.5 μg/mL) and exhibited a very good urease inhibition activity with IC value of 65.03 ± 1.66 μM as compared to standard, thiourea (IC50  = 21 ± 0.11 μM). Strong free radical scavenging activities were observed; it scavenged hydroxyl radical by 95.8% and bleached purple color of DPPH (IC50 : 96.6 μg/mL) at 1.0 mg/mL. In addition, it reduced ferric ion significantly and compared favorably well with ascorbic acid (standard). However, it showed a mild cytotoxic effect on human lung cancer cell line (NCI-H460). The findings suggest that various activities of reflevone may have pharmacological significance against immune disorders, gastrointestinal ulcers and oxidative stress diseases.